Proteksi Overload Motor Universal pada Alat Pengayakan Ulat Hongkong Menggunakan Thermal Overload Relay - Sofiah, Sofiah; Husna, Fadilah; Arafat, M (Universitas PGRI Palembang, 2025)
The rapid growth of pet breeding, such as birds, hamsters, and ornamental fish, has driven the demand forhigh-quality feed to support productivity. One commonly used feed is mealworms, whose screening process is still performed manually. To improve efficiency, an automatic screening tool utilizing a universal motor is required. However, continuous use of the motor can lead to damage due to overload, triggering an increase in current (overcurrent) and a rise in motor temperature. This study aims to protect the universal motor in the mealworm screening machine from overload and excessive temperature increases. The trials were conducted three times, each with five repetitions. The first trial was performed without a load, the second with a constant mealworm load of 4000 grams, and the third with a constant load of 6500 grams. The analysis results indicate that the greater the load borne by the motor, the higher the current and power required. The recommended maximum current for optimal motor operation is 2.2 A, with a maximum load of 4000-5000 grams. Overload protection is essential to prevent motor damage and ensure the screening machine operates efficiently and has a longer service life.